Multicultural Multilegalism – Definition and Challenges - Nielsen, Morten (Les ateliers de l'éthique / The Ethics Forum, 2011)
Multilegalism is a species of legal pluralism denoting the existence of quasi-autonomous “minority jurisdictions” for at least some legal matters within a “normal” state jurisdiction. Multiculturalism in the advocatory sense might provide the justification for establishing such minority jurisdictions. This paper aims to provide 1) a detailed idea about what such a multicultural multilegal arrangement would amount to and how it differs from certain related concepts and legal frameworks, 2) in what sense some standard multicultural arguments could provide a starting point for seriously considering multicultural multilegalism in practice, 3) how the idea fares against some standard liberal criticisms, and finally 4), to point out three salient problems for multilegalism, concerning a) choice of law problems, b) a dilemma facing us as to whether state supremacy should be upheld or not, and c) clashes with basic human rights.